Study on the Transmission Mechanism of Ten Velocity Automatic Transmission - Li Mingsheng; Lan Ying; Li Yong (Jixie chuandong)
The lever method and the planetary gear mechanism of automatic transmission are studied.A new four planetary gear mechanism which is a hybrid institutions concatenated a Ravigneaux mechanism with a Simpson mechanism is constructed.Based on the lever method,its driving route is also analyzed.Seven types of driving ways which can meet with the shifting requirements of the automatic transmission are obtained.Five types of driving ways among them can be used for 9forward gears,and the other two can be applied for 10 forward gears.Therefore,it provides a theoretical reference to develop the multiple-speed transmission system.